Descriptions and prescriptions : values, mental disorders, and the DSMs - Sadler, John Z., 1953- (Johns Hopkins University Press, 2002)
Annotation Most everyone agrees that having pneumonia or a broken leg is always a bad thing, but not everyone agrees that sadness, grief, anxiety, or even hallucinations are always bad things. This fundamental disjunction in how disease and disorders are valued is the basis for the considerations in Descriptions and Prescriptions. In this book John Z. Sadler, M.D., brings together a distinguished group of contributors to examine how psychiatric diagnostic classifications are influenced by the values held by mental health professionals and the society in which they practice. The aim of the book, according to Sadler, is "to involve psychiatrists, psychologists, philosophers, and scholars in related fields in an intimate exchange about the role of values in shaping past and future classifications of mental disorders."Contributors: George J. Agich, Ph. D., Cleveland Clinic Foundation; Carol Berkenkotter, Ph. D., Michigan Technological University; Lee Anna Clark, Ph. D., University of Iowa; K.W.M. Fulford, D. Phil., F.R.C. Psych., University of Warwick, Coventry; Irving I. Gottesman, Ph. D., University of Virginia; Laura Lee Hall, Ph. D.; Cathy Leaker, Ph. D., Empire State College; Chris Mace, M.D., M.R.C. Psych., University of Warwick, Coventry; Laurie McQueen, M.S.S.W., American Psychiatric Association, Washington, D.C.; Christian Perring, Ph. D., Dowling College; James Phillips, M.D., Yale University School of Medicine; Harold Alan Pincus, M.D., University of Pittsburgh School of Medicine; Jennifer H. Radden, D. Phil., University of Massachusetts; Doris J. Ravotas, M.A., L.L.P., Michigan Technological University; Patricia A. Ross, Ph. D., University of Minnesota; Kenneth F. Schaffner, M.D., Ph. D., George Washington University; Michael Alan Schwartz, M.D., Case Western Reserve University; Daniel W. Shuman, J.D., Southern Methodist University; Allyson Skene, Ph. D., York University; Jerome C. Wakefield, D.S.W., Rutgers University; Thomas A. Widiger, Ph. D., University of Kentucky; Osborne P. Wiggins, Ph. D., University of Louisville.